Analyse Applied Linguistics Research Trends in Google Scholar Using A Bibliometric Approach with VOSviewer - Hizbullah, Imam; Fauzi, Ach; Antarsyach, Anelka Almayda; Fathurrahman, Muhammad Albie (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to identify research trends in the field of applied linguistics through bibliometric analysis. This study provides a comprehensive overview of the direction, focus, and productivity of the latest research in applied linguistics. Data collection was conducted on 5 March 2025, utilising the Google Scholar database with the keyword